Oral findings of patients in the Intensive Care Unit: A systematic review - Aranda Gómez, María Paula; Chaparro Torres, Elizabeth; Hernández Abahunza, Nicole Dayanna; Vargas Carreño, Anghela Catalina; Herrera Sandoval, Laura Viviana; Castellanos Domínguez, Yeny Zulay (Revista Cuidarte, 2025)
Highlights • ICU patients face oral health risks due to the use of intraoral devices and poor protocols. • Document specific oral findings in patients with prolonged ICU stays. • The most common oral findings include gingivitis, ulcers, xerostomia, dental caries and periodontitis. • Despite the care provided, common findings such as gingivitis and ulcers highlight the need for dental intervention in ICU patients. Introduction: Patients in intensive care units often experience a decline in oral health. Systematic reports of oral findings in these patients are scarce. Objective: To document oral cavity lesions in patients in Intensive Care Units. Materials and Methods: A systematic review was conducted, with a literature search across five databases, focusing on publications from 2018 to 2023. The identified articles were imported into the Mendeley reference manager; titles and abstracts were reviewed in pairs and under blinded conditions. Pre-selected articles were exported to the Rayyan application for eligibility assessment. Quality of the studies was assessed using the Joanna Briggs Institute (JBI) tool. This research is classified as risk-free and complies with copyright regulations by exercising citation rights (Law 1915 of 2018 and Law 1032 of 2006). Results: A total of 1553 articles were identified. Using the PRISMA methodology, 11 studies were included, with 54% retrieved from PubMed and 91% published in English. Toothbrushing was the most frequently documented oral care procedure. Gingivitis and ulcers were the most frequent oral findings. Discussion: The literature confirms the presence of oral findings in these patients, which are related to their systemic health status, procedures, equipment, and oral health care protocols. Conclusion: Although oral care is provided at a high rate in critically ill patients, oral alterations and lesions are frequently observed. The involvement of a dentist is essential for the comprehensive care of these patients. How to cite this article: Aranda Gómez María Paula, Chaparro Torres Elizabeth, Hernández Abahunza Nicole Dayanna, Vargas Carreño Anghela Catalina, Herrera Sandoval Laura Viviana, Castellanos Domínguez Yeny Zulay. Oral findings of patients in the Intensive Care Unit: A systematic review. Revista Cuidarte. 2025;16(1):e3959. https://doi.org/10.15649/cuidarte.3959